Linguistic Understanding of the Image of the "Mother" in English and French Literature - Garibashvili, Manana; Tkemaladze, Inga; Kochauri, Maka ("Intercultural Dialogues" Transactions, 2023)
The image of the mother is immensely important both in literature and culture all over the universe. Mother is the bedrock and the symbol of life. That’s why the image of mother is frequently depicted in fiction literature by various authors whose principal role is to raise the mother’s image to the level of character which is not an easy task to be done at all. The writer should tend to harmonize the features of the mother, which in most cases are similar in every nation, and create a highly sensitive text which will possibly express and highlight all the important pragmatic features of the mother. It is important to mention that mothers are rarely negatively characterized by the writers in the literature of any country because the mother is considered to a source of inspiration for many writers, no matter what era or literary movements do they belong to. The goal of this study is the analysis of the image of the mother based on the literary texts belonging to the English and French literature. For this reason, we have identified certain texts i.e. literary works. Thus, we aim to make linguistic analysis and more specifically stylistic analysis of the portrayal of the mother from the English and French literature. Based on our findings we will try to discover and outline the general qualities of the mother and motherhood and the ways how they are represented throughout the texts.